ROLE OF DEED LAND BUILDERS OFFICERS (PPAT) IN ADDRESSING PROBLEM FOR REGISTRATION OF TRANSFER PROPERTY DUE TO SALE OF LAND IN EAST KOLAKA - Bambang Suprayogi; Akhmad Khisni (Jurnal Akta, 2019)
This study aims to determine the responsibility of the Land Deed Official (PPAT) in addressing the problems of making a deed of sale of land and how the legal consequences of the public in making the deed of sale of land if found problems in the manufacturing process PPAT deed East Kolaka District. The data used in this study are primary data, secondary data and data that can support tertiary study, then analyzed with empirical juridical methods.Based on the results of this study concluded that the role of PPAT in Kolaka East have a stake in ensuring legal certainty transitional registration of property rights to land. Legal guarantee evidenced by an authentic act, then the transition has a strong legal force (not absolute). However, due toThe lack of public knowledge relevant authorities in givingcertainty and legal protection, it is often raised issues such as land disputes and others.So should their ideal concept for the community in the form of legal counseling in growing knowledge about the importance of Land Registry as a form of awareness of legal action against the sale and purchase of land ownership before PPAT to avoid land disputes that often arise in the future. In addition, there is still much to be understood by the Land Deed Official (PPAT) and the community in the Land Registry. Conversely, if the certificate-issuing PPAT deed of sale is not in accordance with the procedure, it is charged with the responsibility PPAT legal and administrative responsibilities. Keywords : Land Deed Official (PPAT), buying and selling, East Kolaka